Salud oral en comunidad indígena infantil (Yukpa) asentados en el barrio El Escobal de la ciudad de Cúcuta (2024)
Oral health is a fundamental component of general well-being, especially in vulnerable populations such as indigenous communities, among them, the Yukpa ethnic group, which is located in the city of Cúcuta, specifically in the El Escobal neighborhood, these communities face significant challenges in regarding your oral health. These challenges are the result of a combination of socioeconomic, cultural and geographic factors that limit access to adequate health services and oral hygiene education and prevention programs. Yukpa children, in particular, are a vulnerable group. The prevalence of oral diseases, such as dental caries, is high among children in this community, which affects not only their physical health but also their development and quality of life. The lack of health infrastructure, the shortage of specialized health professionals, the language and cultural barrier are obstacles that prevent access to adequate dental care. This work aims to determine the status of carious lesions in the indigenous children's community, evaluate the rate of dental caries using the DMFT and CEOD index, analyze and promote oral hygiene practices among school children and their parents in the Yukpa community and Implement the application of fluoride in varnish and caries removal using the Atraumatic Restorative Treatment (ART) technique, by understanding and addressing the specific needs of Yukpa children, you can contribute to improving their quality of life and promoting healthy development within their cultural and social environment.